2003
DOI: 10.1007/s00449-003-0340-2
|View full text |Cite
|
Sign up to set email alerts
|

Film analysis of activated sludge microbial discs by the Taguchi method and grey relational analysis

Abstract: A biofilm model with substrate inhibition is proposed for the activated sludge growing discs of rotating biological contactor (RBC); this model is different from the steady-state biofilm model based on the Monod assumption. Both deep and shallow types of biofilms are examined and discussed. The biofilm models based on both Monod and substrate inhibition (Haldane) assumptions are compared. In addition, the relationships between substrate utilization rate, biofilm thickness, and liquid phase substrate concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…(8). For this study, the value of is selected as 0.5 [3], and the observed values were summarized in Table 4. Table 5 lists the grey relational coefficient and grade for each experiment of the experimental arrangement calculated by applying Eqs.…”
Section: Optimal Combination Of the Process Parametersmentioning
confidence: 99%
“…(8). For this study, the value of is selected as 0.5 [3], and the observed values were summarized in Table 4. Table 5 lists the grey relational coefficient and grade for each experiment of the experimental arrangement calculated by applying Eqs.…”
Section: Optimal Combination Of the Process Parametersmentioning
confidence: 99%
“…The simulation was implemented to analyze the effects of various levels of transport limitation on a growing single-species biofilm. A mathematical model that simulates biofilm thickness, liquid phase substrate concentration, and substrate utilization rate in RBCs was developed (Chen and Syu, 2003 (Gheewala and Annachhatre, 2003). Inhibitions on biofilm growth due to substrate, secondary substrate, and product were considered.…”
Section: Growth and Modelingmentioning
confidence: 99%
“…Results of GRA are based on original data and the calculations are simple and easy to understand. Grey system theory has been applied to various systems such as biofilm (Chen and Syu 2003), agronomy (Huang et al 2003), traditional Chinese medicine (Wang et al 2004), food industry and gastroenterology (Tan et al 2005). In the present study, a GRA calculation procedure is demonstrated step-by-step and results are compared with the results of PB design to analyze the grades of influence of the affecting factors on the yield of recombinant CYP2C9.…”
Section: Introductionmentioning
confidence: 99%